(untitled) (Bangladesh Journal of Urology, 2023)
Background: Transurethral resection of bladder tumour (TURBT) is considered as the gold standard in the surgical management of bladder tumour despite impressive advancement in en-bloc resection. However, the optimum method for resection of bladder tumour is yet to be established. Objectives: This study has been designed to compare the outcome of en-bloc resection versus conventional resection of bladder tumour of superficial transitional cell carcinoma of urinary bladder patients. Methods: This interventional study was carried out in the department of Urology, National Institute of Kidney Diseases and Urology, Dhaka from May 2020 to April 2021. Sixty Patients were selected by purposive sampling technique and allocated into two groups as group A- en-bloc resection and group B- conventional resection by randomization. All even numbers were select for ERBT and all odd Numbers for cTURBT. Results: Volume of irrigation fluid (p = 0.001) and duration of operation (p= 0.024) were significant between ERBT and cTURBT. However, 3, 6, 9-month recurrence rate was not statistically significant between ERBT and cTUTBT. The incidence of complications such as obturator nerve reflex (p = 0.222) and bladder perforation (p = 0.301) were less frequent in the ERBT group. Mean duration of postoperative hospital stay in group A and group B were 3.38±1.12 and 3.57±1.23 days respectively, this difference was statistically not significant (p>0.05). There was no significant difference in categorical data between groups. Conclusion: This study shows in comparison to conventional resection en-bloc resection shortens per operative complications, duration of operation & hospital stay and recurrence status during follow up. Bangladesh J. Urol. 2023; 26(2): 84-90